Bismuth(III) dication trapped on a chlorobismuthate. Issue 8 (18th April 2019) - Balasubramaniam, Selvakumar; Varghese, Babu; Venugopal, Ajay
Abstract: Metal cations observed with tetrachloroaluminate anion provide insights into the structure and stability of reactive cations. Addition of tris(3, 5-dimethylpyrazolyl)borate anion (Tp Me2 ) to [BiCl2 ][AlCl4 ] traps a bismuth(III) dication, [Tp Me2 Bi] 2+, possessing a highly electrophilic bismuth center with short coordinate Bi―N bonds. [Tp Me2 Bi] 2+ has weak interactions with the chlorides of [Bi3 Cl13 ]∞ . Strong affinity of [Tp Me2 Bi] 2+ with the triflate (OTf) observed in [Tp Me2 Bi(OTf)3 ] - demonstrates the high electrophilicity at bismuth. Graphical Abstract: